Hexagonal single crystal domains of few-layer graphene on copper foils. - Robertson, A; Warner, J (2011)
Hexagonal-shaped single crystal domains of few layer graphene (FLG) are synthesized on copper foils using atmospheric pressure chemical vapor deposition with a high methane flow. Scanning electron microscopy reveals that the graphene domains have a hexagonal shape and are randomly orientated on the copper foil. However, the sites of graphene nucleation exhibit some correlation by forming linear rows. Transmission electron microscopy is used to examine the folded edges of individual domains and reveals they are few-layer graphene consisting of approximately 5-10 layers in the central region and thinning out toward the edges of the domain. Selected area electron diffraction of individual isolated domains reveals they are single crystals with AB Bernal stacking and free from the intrinsic rotational stacking faults that are associated with turbostratic graphite. We study the time-dependent growth dynamics of the domains and show that the final continuous FLG film is polycrystalline, consisting of randomly connected single crystal domains.